Green Intellectual Capital and Corporate Environmental Performance: Does Environmental Management Accounting Matter? - Musaab Alnaim; Abdelmoneim Bahyeldin Mohamed Metwally (Administrative Sciences, 2024)
This study investigates the relationship between green intellectual capital and corporate environmental performance, with a specific focus on the moderating role of environmental management accounting. Data were collected from a sample of 298 employees working in the Egyptian industrial sector and analyzed using smart partial least squares (SmartPLS) software. The empirical results revealed a statistically positive and significant impact of all green intellectual capital components on corporate environmental performance, indicating that green intellectual capital is a critical determinant in enhancing environmental performance. Further, the analysis reveals that environmental management accounting functions as a significant moderator in the relationship between green intellectual capital and corporate environmental performance. The model explains 80.2% of the variance in corporate environmental performance, providing strong empirical support for this study’s hypotheses. These findings have important practical implications for companies working in the Egyptian context. They can help in guiding the development of corporate policies and strategies that improve environmental performance. This research also makes a significant contribution to the literature by being one of the first to study the moderating role of environmental management accounting practices in an emerging market like Egypt, as most early studies have concentrated on the direct relationship between green intellectual capital, environmental management accounting, and corporate environmental performance. This helps in better understanding of these concepts and how they interact.